Intrauterine Herpes Simplex Virus Infection Presenting as a Zosteriform Eruption in a Newborn - Caitlin M. Drumm; Maura C. Caufield; Cynthia M. DeKlotz; Helena B. Pasieka; Kabir M. Abubakar (Thieme Medical Publishers, Inc., 2018)
There is significant morbidity and mortality associated with the transmission of herpes simplex virus (HSV) from pregnant women to their fetus or newborn. Although most commonly transmitted in the peripartum period, in rare cases HSV can lead to intrauterine infection. Cutaneous lesions are the most common manifestation of intrauterine HSV, and have a wide spectrum of presentation. We present a rare case of intrauterine HSV-2 infection presenting with a zosteriform eruption mimicking congenital varicella syndrome in a newborn.